PKDL--A Silent Parasite Pool for Transmission of Leishmaniasis in Kala-azar Endemic Areas of Malda District, West Bengal, India. - Swagata Ganguly; Pabitra Saha; Moytrey Chatterjee; Surajit Roy; Tamal Kanti Ghosh; Subhasish K Guha; Pratip K Kundu; Dilip K Bera; Nandita Basu; Ardhendu K Maji (Public Library of Science (PLoS), 2015)
Post Kala-azar Dermal Leishmaniasis (PKDL) is a chronic but not life-threatening disease; patients generally do not demand treatment, deserve much more attention because PKDL is highly relevant in the context of Visceral Leishmaniasis (VL) elimination. There is no standard guideline for diagnosis and treatment for PKDL. A species-specific PCR on slit skin smear demonstrated a sensitivity of 93.8%, but it has not been applied for routine diagnostic purpose. The study was conducted to determine the actual disease burden in an endemic area of Malda district, West Bengal, comparison of the three diagnostic tools for PKDL case detection and pattern of lesion regression after treatment. The prevalence of PKDL was determined by active surveillance and confirmed by PCR based diagnosis. Patients were treated with either sodium stibogluconate (SSG) or oral miltefosine and followed up for two years to observe lesion regression period. Twenty six PKDL cases were detected with a prevalence rate of 27.5% among the antileishmanial antibody positive cases. Among three diagnostic methods used, PCR is highly sensitive (88.46%) for case confirmation. In majority of the cases skin lesions persisted after treatment completion which gradually disappeared during 6-12 months post treatment period. Reappearance of lesions noted in two cases after 1.5 years of miltefosine treatment. A significant number of PKDL patients would remain undiagnosed without active mass surveys. Such surveys are required in other endemic areas to attain the ultimate goal of eliminating Kala-azar. PCR-based method is helpful in confirming diagnosis of PKDL, referral laboratory at district or state level can achieve it. So a well-designed study with higher number of samples is essential to establish when/whether PKDL patients are free from parasite after treatment and to determine which PKDL patients need treatment for longer period.